The Role of Teachers in Dealing with Separation Anxiety Disorder in Early Childhood in Preschool - Siti Wulan Darnia; Hayani Wulandari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Separation anxiety disorder is a situation where a family experiences a breakdown or a broken household, a family or household situation without the presence of one of the parents (father or mother) caused by death and divorce. The many problems in children who experience separation anxiety disorder can affect the child both physically and psychologically. This research aims to examine the role of teachers in the Purwakrta area using questionnaire research instruments and questionnaires via Google Form. Analysis of data obtained from interviews and questionnaires, analyzed qualitatively to identify themes and patterns related to teacher responses to children who experience separation anxiety. Analysis was carried out using a descriptive approach to provide a comprehensive picture. The results of this research are aimed at finding out the role of teachers in dealing with separation anxiety disorder. The teacher's role in dealing with separation anxiety disorders in early childhood is as the first counseling process in terms of informer, motivator, facilitator, mediator and evaluator.